Pembaca dan Interaksi Teks: Respons Pembaca terhadap Alur Melingkar dalam Kisah-kisah tentang Sherlock Holmes - Devara, Gina Hanifa (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
This research discusses how the readers’ responses to plot twists in several Sherlock Holmes stories influence their reading interest and curiosity in other Sherlock Holmes stories and other mystery works. The aim is to find the relationship between knowledge of the plot and interest in reading Sherlock Holmes books among English Department students at Andalas University, 2022 generation. The results show that most respondents were familiar with plot twists and mystery stories. It proves that the students think plot twists in stories are trendy and can increase their interest in reading other mystery stories.